2010
DOI: 10.1007/s00415-010-5858-z
|View full text |Cite
|
Sign up to set email alerts
|

Camptocormia phenotype of FSHD: a clinical and MRI study on six patients

Abstract: Recently it has been postulated that there is an atypical facioscapulohumeral muscular dystrophy (FSHD) phenotype with isolated axial myopathy. Involvement of paraspinal and limb muscles was evaluated in six patients with molecularly proven FSHD and a predominant bent spine phenotype. Consistent with the camptocormia phenotype, the most severely affected muscles in all six patients were the thoracic and lumbar spinal tract together with hamstrings. MRI disclosed severe axial muscle degeneration but mostly subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
22
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 47 publications
(78 reference statements)
5
22
1
1
Order By: Relevance
“…Jordan et al presume that a weakness of hamstrings might contribute to camptocormia. Our findings do not show a marked affection of the hip extension (gluteus maximus) either clinically or in MRI, but we could detect a marked affection of the knee flexion (semimembranosus) clinically and in MRI [33]. Our findings are in good agreement with the results of Olsen et al [16] who reported a significant correlation between muscle strength and fatty MRI degeneration in the hip and thigh muscles, including MRI affection of some leg muscles despite normal function on manual testing.…”
Section: Other Correlationssupporting
confidence: 83%
“…Jordan et al presume that a weakness of hamstrings might contribute to camptocormia. Our findings do not show a marked affection of the hip extension (gluteus maximus) either clinically or in MRI, but we could detect a marked affection of the knee flexion (semimembranosus) clinically and in MRI [33]. Our findings are in good agreement with the results of Olsen et al [16] who reported a significant correlation between muscle strength and fatty MRI degeneration in the hip and thigh muscles, including MRI affection of some leg muscles despite normal function on manual testing.…”
Section: Other Correlationssupporting
confidence: 83%
“…Erector spinae muscle weakness can rarely cause ‘bent spine syndrome’ (camptocormia) 10. The combined weakness of abdominal and back muscles is an important contributor to patients’ loss of balance and subsequent falling 11.…”
Section: Symptoms and Signsmentioning
confidence: 99%
“…Patients can develop debilitating paraspinal muscle weakness, which can be an initial presentation. 10 Although the most common presentation is with facial and shoulder weakness and a descending pattern of progression, many different initial presentations have been described, including bent-spine and less specific limb girdle patterns. The rate of progression has been evaluated in a large prospective natural history study, which demonstrated a loss of strength using combined quantitative strength testing and manual muscle testing of about 1-4% per year.…”
Section: Clinical Findingsmentioning
confidence: 99%